Two self-critiques in Heidegger's critique of metaphysics - Gilliland, R. (Journal of Speculative Philosophy, 2012)
This article traces shifts in Heidegger's stance toward metaphysics after fundamental ontology and argues that these shifts reflect changes in his conceptions of ontological difference and temporality that pave the way for his mature thought. Copyright © 2012 The Pennsylvania State University.
Keywords: dept.phi; ⚠️ Invalid DOI

A psychoanalyst on the couch - Nasio, J.-D.; Raffoul, F.; Pettigrew, D. (A Psychoanalyst on the Couch, 2012)
An interview with Juan-David Nasio. In A Psychoanalyst on the Couch, we find the noted psychoanalyst and Lacan commentator Juan-David Nasio on the analyst's couch himself. In the interview that makes up this book, he provides insight into his forty-year career as a writer and practitioner, elaborating on Freudian and Lacanian concepts important to his work and reflecting on broad issues related to psychology and culture-as well as personal remembrances. The result is an intimate and wide-ranging look at the man and thinker, both an introduction to his work and a deeper look at his approach and outlook. © 2012 State University of New York. All rights reserved.
Keywords: dept.phi

The task of justice - Pettigrew, D. (Jean-Luc Nancy and Plural Thinking: Expositions of World, Ontology, Politics, and Sense, 2012)
Keywords: dept.phi

The Factor of Listening in Karl Jaspers’ Philosophy of Communication - Górniak-Kocikowska, Krystyna (Philosophical Faith and the Future of Humanity, 2012)
Jaspers’ views on communication and his approach to the question of listening, both underwent an evolution in which World War II and the first years thereafter played a crucial role. In this process, Jaspers journeyed from listening to the great minds of the past, through an inward dialogue with them, to one-sided lecturing while his audience was engaged in a straight-line listening, to an intimate dialogue with those he considered like-minded, to a multi-faceted dialogue, and finally to listening to his contemporaries and learning how to practice transactional listening-in-conversation in the process of a multi-layered communication he called a loving struggle. This evolution, paralleled by the transition of Japers’ philosophy from local-centered to world-centered makes his thinking attractive and useful today.
Keywords: German Student; Great Mind; Nazi Regime; Political Involvement; Verbal Communication; dept.phi